Comparison of intensive and low-dose atorvastatin therapy in the reduction of carotid intimal–medial thickness in patients with coronary heart disease. Issue 8 (7th March 2007) - Yu, Cheuk-Man; Zhang, Qing; Lam, Linda; Lin, Hong; Kong, Shun-Ling; Chan, Wilson; Fung, Jeffrey Wing-Hong; Cheng, Kenny K K; Chan, Iris Hiu-Shuen; Lee, Stephen Wai-Luen; Sanderson, John E; Lam, Christopher Wai-Kei
Abstract : Background: Intensive statin therapy has been shown to improve prognosis in patients with coronary heart disease (CHD). It is unknown whether such benefit is mediated through the reduction of atherosclerotic plaque burden. Aim: To examine the efficacy of high-dose atorvastatin in the reduction of carotid intimal–medial thickness (IMT) and inflammatory markers in patients with CHD. Design: Randomised trial. Setting: Single centre. Patients: 112 patients with angiographic evidence of CHD. Interventions: A high dose (80 mg daily) or low dose (10 mg daily) of atorvastatin was given for 26 weeks. Main outcome measures: Carotid IMT, C-reactive protein (CRP) and proinflammatory cytokine levels were assessed before and after therapy. Results: The carotid IMT was reduced significantly in the high-dose group (left: mean (SD), 1.24 (0.48) vs 1.15 (0.35) mm, p = 0.02; right: 1.12 (0.41) vs 1.01 (0.26) mm, p = 0.01), but was unchanged in the low-dose group (left: 1.25 (0.55) vs 1.20 (0.51) mm, p = NS; right: 1.18 (0.54) vs 1.15 (0.41) mm, p = NS). The CRP levels were reduced only in the high-dose group (from 3.92 (6.59) to 1.35 (1.83) mg/l, p = 0.01), but not in the low-dose group (from 2.25 (1.84) to 3.36 (6.15) mg/l, p = NS). A modest correlation was observed between the changes in carotid IMT and CRP (r = 0.21, p = 0.03). Conclusions: In patients with CHD, intensive atorvastatin therapy results in regression of carotid atherosclerotic disease, which is associated with reduction in CRP levels. On the other hand, a low-dose regimen only prevents progression of the disease.